Modelling Demand Side Kelas Menengah Pemuda Kota Surabaya - Achmadi, Achmadi; Prihantono, Gigih (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82), 2014)
Middle class is an interesting topic in social studies to do a research. Based on Mckenzie, there are currently 45 million people in Indonesia can be categorized as middle class, and in 2030 will reach 135 million people. The middle class is the biggest support of drive economic growth from the demand side. This study aims to perform a simple modeling of middle-class’s cuncumption behavior, which study middle-class subculture in the city of Surabaya. This study uses an econometric tool called the logistic regression with two purchases decision, impulse buying and planned buying, as dependent variables in the model. Results of this study also show that the income effect variables, motivational variables and variable materialistic values ??consume has a significant and positive effect on impulse buying purchasing decisions. While product involvement variable have positive influence on planned purchases buying behavior.
Keywords: modelling; demand side; middle class; youth